1999
DOI: 10.1093/humrep/14.6.1555
|View full text |Cite
|
Sign up to set email alerts
|

Effects of follicle-stimulating hormone and serum substitution on the in-vitro growth of human ovarian follicles

Abstract: In-vitro maturation (IVM) of human ovarian follicles and oocytes could benefit infertile women, and allow the development of in-vitro systems for the study of human follicular development. Little is known about the initiation of growth of primordial follicles and the regulation of early folliculogenesis. An ovarian tissue-slice culture system was used to examine the effects of media composition, follicle stimulating hormone (FSH) and serum substitution on the development of small human follicles in vitro. Huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
123
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(141 citation statements)
references
References 37 publications
12
123
0
6
Order By: Relevance
“…The effects of cAMP on follicle development in the present study were in accordance with those obtained by using FSH supplementation (2). FSH supplementation did not increase the diameters of the follicles or promote the developmental stages during the first 5 days of culture.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The effects of cAMP on follicle development in the present study were in accordance with those obtained by using FSH supplementation (2). FSH supplementation did not increase the diameters of the follicles or promote the developmental stages during the first 5 days of culture.…”
Section: Discussionsupporting
confidence: 90%
“…It would be interesting to test combined effect of cAMP and FSH on the early human ovarian follicles. FSH is involved in early folliclulogenesis in human (2). In human, 50% of follicles at the primary stage express FSH receptor (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the other treatments (FSH-7d and FSH + FGF-2) were effective in maintaining follicle ultrastructural integrity up to day 7. Our light histological results confirm earlier studies in which FSH maintained preantral follicle viability after short (Matos et al, 2007a andMatos et al, 2007c) or long-term culture (Cortvrindt et al, 1997, Wright et al, 1999and Gutierrez et al, 2000. It is suggested that the absence of FSH in the medium could compromise the diffusion of several essential chemical and physical factors through the basement membrane (Hsueh et al, 1994).…”
Section: Discussionsupporting
confidence: 89%
“…As there are FSH receptors in the granulosa cells of early follicles, it is possible that FSH may promote follicular growth and development (Méduri et al, 2002). Previous observations have showed that FSH promotes an increase in both oocyte (Itoh et al, 2002) and follicular diameter (Wright et al, 1999) after long-term culture.…”
Section: Discussionmentioning
confidence: 99%